Cratonic Reactivation in the Precambrian Basement of Western Canada. III. Crustal Evolution - Burwash, R. A.; Krupička, J.; Culbert, R. R. (Canadian Journal of Earth Sciences, 1973)
Relative to the Superior and Slave provinces, the Churchill province is enriched in K and Rb. The inferred mechanism of alkali enrichment involves diapiric uprise of mantle material from the base of the low velocity zone, in response to upward movement of water from the deep mantle. Intergranular fluid in the peridotite is enriched in K and Rb. At the base of the crust this fluid separates to enter deep-seated crustal shear zones. At upper crustal levels, reaction with permeable cataclasites causes K-metasomatism, involving especially the change of plagioclase into K-feldspar.Eclogite bodies within the peridotite, on moving upward to the base of the crust yield andesitic magma which separates to form sialic underplating. The existence of a discrete lower crust beneath southern Alberta, western Ontario, and northern Manitoba is shown by deep crustal reflection and refraction seismic studies.Generation of juvenile sial during the Hudsonian orogeny is indicated by initial ratios of whole-rock Rb–Sr isochrons for igneous rocks. During metasomatism, potassium and rubidium were added in the ratio of about 350:1. This ratio makes it unlikely that these alkalis were derived by anatexis of Kenoran crystalline basement.